Predictors of prolonged length of hospital stay and in-hospital mortality in patients aged 1-24 months with acute bronchiolitis in Douala, Cameroon - Charlotte Eposse Ekoube; Emmanuel Heles Nsang; Patricia Épée; Edgar Mandeng Ma Linwa; Yolande Djike Puepi; Ritha Mbono Betoko; Diomède Noukeu Njinkui; Dominique Enyama; Dora Mbonjo Bitsie; Jeannette Disso Massako; Soumaiyatou Abba; Esther Eleonore Ngo Linwa; et al. (BMC, 2024)
Abstract Introduction In Cameroon, acute bronchiolitis has been reported as the third commonest lower respiratory infection and is usually associated with low mortality. Nonetheless, respiratory distress associated with non-adherence to management guidelines can prolong hospital stay. This study aimed to explore predictors of prolonged hospital stay (≥ 5 days) and mortality in patients aged < 2years hospitalised for acute bronchiolitis. Methodology We conducted a retrospective cohort study at three paediatric units in the city of Douala, Cameroon. Factors associated with prolonged hospital stay and mortality were determined using multivariable linear regression model. Threshold for significance was set at p ≤ 0.05. Results A total of 215 patients with bronchiolitis were included with mean age of 6.94 ± 5.71 months and M/F sex ratio of 1.39/1. Prolonged hospital stay was reported in 46.98% and mortality in 10.70% of patients hospitalised for bronchiolitis. Factors independently associated with prolonged hospital duration were oxygen administration [b = 0.36, OR = 2.35 (95% CI:1.16-4.74), p = 0.017], abnormal respiratory rate [b = 0.38, OR = 2.13 (1.00-4.55), p = 0.050] and patients presenting with cough [b = 0.33, OR = 2.35 (95% CI: 1.22-4.51), p = 0.011], and diarrhoea [b = 0.71, OR = 6.44 (95% CI: 1.6-25.86), p = 0.009] on admission. On the other hand, factors independently associated with mortality were age of the patient [b= -0.07, OR = 0.84 (95% CI: 0.74-0.97), p = 0.014] and oxygen administration [b = 1.08, OR = 9.64 (95% CI:1.16-79.85), p = 0.036] Conclusion Acute bronchiolitis represented 1.24% of admissions and was common in the rainy season, in males and 3-11-month-old patients. Management guidelines were poorly respected. Prolonged length of stay was reported in half of the patients hospitalized and mortality was high, especially in younger patients and in patients receiving oxygen.